An electromyographic study of the effect of hand grip sizes on forearm muscle activity and golf performance - Sorbie, G. S.; Hunter, H. H.; Grace, F. M. (Research in Sports Medicine, 2016)
The study describes the differences in surface electromyography (EMG) activity of two forearm muscles in the lead and trail arm at specific phases of the golf swing using a 7-iron with three different grip sizes among amateur and professional golfers. Fifteen right-handed male golfers performed five golf swings using golf clubs with three different grip sizes. Surface EMG was used to measure muscle activity of the extensor carpi radialis brevis (ECRB) and flexor digitorum superficialis (FDS) on both forearms. There were no significant differences in forearm muscle activity when using the three golf grips within the group of 15 golfers (p > 0.05). When using the undersize grip, club head speed significantly increased (p = 0.044). During the backswing and downswing phases, amateurs produced significantly greater forearm muscle activity with all three grip sizes (p < 0.05). In conclusion, forearm muscle activity is not affected by grip sizes. However, club head speed increases when using undersize grips.